Computational polarization 3D: New solution for monocular shape recovery in natural conditions. (April 2022) - Han, Pingli; Cai, Yudong; Liu, Fei; Li, Xuan; Liang, Rongguang; Yan, Mingyu; Shao, Xiaopeng
Highlights: Monocular 3D imaging based upon polarization properties of reflected light. Separating mixed specular and diffuse reflection, making the method working for non-Lambertian surface. Correction to azimuth ambiguity problem in polarization 3D imaging. Abstract: Analyzing the polarimetric properties of the reflected light is a simple, fast, and low-cost approach to recover shape information, but no reported method can accurately recover surface shape from non-Lambertian object in natural conditions with a single view. Another major issue is the lack of effective methods to address azimuth ambiguity during the surface reconstruction. To address these two major obstacles, we propose a monocular 3D polarization imaging approach for non-Lambertian surfaces by investigating the subtle difference in specular and diffuse reflection and then separating them using independent component analysis (ICA). Separated pure diffuse reflection enables accurate polarization extraction, based on which a gradient field is derived to determine surface normals. The ambiguity is removed by solving an optimization problem with a reference gradient field. We experimentally demonstrate the performance of the proposed method with man-made objects under controlled illumination and human face under natural illumination.